Adverse life events, cardiovascular responses, and sports performance under pressure - Moore, L. J.; Young, T.; Freeman, P.; Sarkar, M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Research suggests that experiencing a moderate number of adverse life events can benefit future stress responses. This study explored the relationship between adverse life (i.e., non-sport) events and cardiovascular responses to, and performance during, a pressurized sporting task. One hundred participants (64 men, 36 women; Mage = 21.94 years, SDage = 4.98) reported the number of adverse life events (e.g., serious accident or injury) they had encountered before completing a pressurized dart-throwing task during which performance was recorded. Before the task, participants` demand and resource evaluations and cardiovascular reactivity were assessed. Adverse life events did not impact demand and resource evaluations. However, participants who reported 4-7 adverse life events displayed cardiovascular responses more reflective of a challenge state (relatively lower total peripheral resistance and/or higher cardiac output) compared to those who reported a lower (<4) or higher (>7) number of events. Furthermore, participants who reported 3-13 adverse life events outperformed those who reported a lower (<3) or higher (>13) number of events. Supplementary analyses suggested that this relationship might be due to a small number of extreme values. However, after outlier analyses, a significant linear relationship remained suggesting that a higher number of adverse life events facilitated performance. The results suggest that experiencing a moderate to high number of adverse life events might have beneficial effects on subsequent cardiovascular responses and performance under pressure. Practitioners should therefore consider prior brushes with adversity when identifying athletes who are likely to excel during stressful competition.